Biological Control of Solenopsis Fire Ants by Pseudacteon Parasitoids: Theory and Practice - Lloyd W. Morrison (Psyche: A Journal of Entomology)
Pseudacteon parasitoids are potential biocontrol agents of invasive Solenopsis fire ants. Pseudacteon species that parasitize the invasive S. invicta Buren and S. richteri Forel have been introduced to, and naturally dispersed across, the southeastern USA, although there is no evidence yet that Solenopsis host ant populations have decreased. The ability of introduced Pseudacteon species to regulate Solenopsis populations will depend upon the relative importance of top-down effects in the recipient communities. In this paper, I examine the characteristics of the Pseudacteon/Solenopsis parasitoid/host system and evaluate the extent to which research findings are consistent with top-down control. Laboratory and field experiments evaluating Solenopsis population regulation have been equivocal, and overall the available evidence provides little support for strong top-down effects in this system. Competitive exclusion may occur among introduced Pseudacteon species, and future efforts at biological control are likely to be more efficacious if they focus on other types of natural enemies.